Media Herpetofauna sebagai Pengayaan Pengetahuan Bagi Guru Sekolah Dasar (SD) di Lingkungan Desa Hambalang, Bogor - Hanum Isfaeni; Ratna Dewi Wulaningsih; Muhamad Isnin Noor (Universitas Indraprasta PGRI, 2022)
Biodiversity in the environment around communities and schools is an important resource asset for human life as well as in school learning activities. One of the biodiversity that exists in the environment around the human area, namely animals belonging to the category of amphibians and reptiles (herpetofauna groups). The population of herpetofauna animals in Indonesia tends to decline continuously, due to various factors such as habitat loss and other pressures or disturbances. The existence of herpetofauna in agricultural, plantation and residential areas actually has a very strategic role in the balance of nature. Conservation of herpetofauna animals must be introduced to the community, especially the next generation around the area. One of the community groups (the younger generation) that has great potential in herpetofauna conservation activities, namely elementary school students (SD). Conservation education for the next generation (SD students) can be well implemented through good learning methods and media by their teachers. The use of herpetofauna media in teaching science, environment or local content is still minimal. Knowledge of hepetofauna conservation for teachers is still relatively low. The utilization and availability of science or environmental learning media at the elementary school level is still relatively lacking.